2021
DOI: 10.1007/s00170-021-07909-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the polishing mechanism of magnetorheological elastic polishing composites

Abstract: Computer-controlled ultra-precision polishing technology is widely used for high-quality surface processing. However, its polishing tool has some shortcomings, such as limited adaptability to the complex surface and easy to cause surface damage. Therefore, a new smart material-based abrasive tool named magnetorheological elastic polishing composites (MREPCs) and its flexible polishing method are proposed.This study first prepared MREPCs and developed a polishing tool for MREPCs. Then, the material properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To suppress the vibration during turning process, Vasanth et al [20] developed an MRE damper and determined the optimal cutting parameters, and the experimental results showed that the tool vibration was mitigated by 60% and the cutting performance was improved significantly. Xu et al [21] proposed a new smart material-based abrasive tool using the MRE composites to restrain the vibration in polishing, and experimental results demonstrated that the MRE had broad application prospects in ultra-precision machining of complex small parts.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the vibration during turning process, Vasanth et al [20] developed an MRE damper and determined the optimal cutting parameters, and the experimental results showed that the tool vibration was mitigated by 60% and the cutting performance was improved significantly. Xu et al [21] proposed a new smart material-based abrasive tool using the MRE composites to restrain the vibration in polishing, and experimental results demonstrated that the MRE had broad application prospects in ultra-precision machining of complex small parts.…”
Section: Introductionmentioning
confidence: 99%
“…As a polishing tool, an MRE can be used to control the polishing efficiency and quality by adjusting its hardness according to the magnetic field strength. Xu et al [7,8] developed an MRE polishing wheel with a silicone rubber matrix to polish titanium alloy workpieces, showing that applying a magnetic field can increase the hardness of the MRE and subsequently help obtain superior workpiece surface quality. Chen et al [9] developed a ring-shaped polishing wheel tool to polish optical glasses and found that the higher shear strength of the MRE contributed to the formation of polished band patches with superior material removal compared with that of magnetorheological fluid polishing.…”
Section: Introductionmentioning
confidence: 99%